The relationship between q-SOFA score and mortality of sepsis patients at Jogja Hospital - Pramono, Ardi; Rahmat, Basuki; Nurchalifah, Jessenia Eldora; Geofany, Shania Ardelia (Institute of Computer Science (IOCS), 2024)
Sepsis and severe sepsis are the leading causes of death in critically ill patients admitted to intensive care units (ICUs) in the United States. The national economic burden for sepsis in Indonesia at 100,000 patients is estimated to reach USD 130 million. Currently, screening for patients who may have sepsis has also been used frequently. The assessment can be done with a qSOFA score measurement (quick SOFA) or rapid measurement. This study used a retrospective with secondary data from medical records of patients treated in the intensive care unit of Jogja Hospital from January through December 2023. The subjects of 62 patients suffering from sepsis were obtained, with 25 patients (40.3%) at low-risk qSOFA values and 37 (59.7%) at high-risk qSOFA values. The results of this study stated that there was no relationship between the patient's qSOFA score when admitted to the hospital and the mortality of sepsis patients in the intensive care unit of the Jogja Hospital (p>0.07). Thus, the results of this study provide important insights for clinical practitioners in evaluating and planning the treatment of sepsis patients, considering that qSOFA, although useful as an initial screening tool, should not be used as the sole factor in clinical decision-making regarding the management of sepsis patients.